Long-term shareholder perks and stock price reaction. - Yao Gao; Yoshiaki Nose (PLoS ONE, 2024)
This study aimed to examine the impact and source of announcements introducing additional long-term shareholder perks on stock prices of Japanese listed companies. We produced more precise analysis results by categorizing the total sample into favorable change and unfavorable change sample. As a result, we found that long-term shareholder perks have a positive impact on stock prices through the expansion of the shareholder base in the case of a favorable change, whereas there is no negative impact on stock liquidity due to an increased number of long term individual shareholders. On the contrary, in the case of an unfavorable change, we found a weak trend of shrinkage in the shareholder base due to individual shareholders' defection and a consequent decrease in stock liquidity. In the case of a favorable change, the long-term shareholder perks program functions as a means to increase the number of shareholders and encourage them to hold the shares for a longer period of time.